COMPARISON OF THE EFFICACY OF NEOADJUVANT CHEMO-RADIOTHERAPY IN TREATMENT OF PATIENTS WITH LOCALLY ADVANCED FORMS OF BREAST CANCER - Голотюк, С. І.; Гнидюк, М. І.; Живецький, В. А.; Голотюк, І. С.; Горошко, С. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
A clinical and morphological study of the effectiveness of neoadjuvant chemotherapy and rhythms of radiation therapy with chemoradiomodification by 5-fluorouracil in the treatment of locally advanced breast cancer patients was conducted. Neoadjuvant chemotherapy with anthracyclines of the CMF scheme and radiation therapy in medium fractions modified by sensitizing doses of 5FU shown to be effective and have higher efficiency than classic radiation therapy.